Beyond pleasurable and meaningful: Psychologically rich entertainment experiences - Dominique S. Wirz; Allison Eden; Ezgi Ulusoy; Morgan E. Ellithorpe (PLoS ONE, 2025)
Entertainment experiences have been conceptualized as hedonic (pleasurable) or eudaimonic (meaningful), mirroring the hedonic and eudaimonic components of psychological well-being. However, psychologists have proposed a third component of well-being: psychological richness, which is characterized by variety, novelty, and interest. In this paper we explore the role of psychological richness in film and television entertainment experiences. Two studies, an experience sampling study (n = 28) and a survey (students in the US, n = 247 and general population in Germany, n = 289) show the prevalence of experience of psychological richness during media use and its positive relationship with well-being. A replication with a different scale (n = 291) demonstrates that psychologically rich entertainment experiences may have been previously been conflated by some measures of eudaimonic entertainment. Incorporating psychologically rich entertainment experiences as a third addition to hedonic and eudaimonic experiences can increase the intervention potential of media used to enhance well-being.